2002
DOI: 10.1079/bjnbjn2002521
|View full text |Cite
|
Sign up to set email alerts
|

Dietary myristic acid modifies the HDL-cholesterol concentration and liver scavenger receptor BI expression in the hamster

Abstract: The influence of myristic acid in a narrow physiological range (0·5 to 2·4 % of total dietary energy) on the plasma and hepatic cholesterol metabolism was investigated in the hamster. The hamsters were fed on a diet containing 12·5 g fat/100 g and 0·05 g cholesterol/100 g with 0·5 % myristic acid (LA diet) for 3 weeks (pre-period). During the following 3 weeks (test period), they were divided into four dietary groups with 0·5 % (LA), 1·2 % (LM), 1·8 % (ML) or 2·4 % (M) myristic acid. Finally, half the hamsters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
0
2

Year Published

2004
2004
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 66 publications
(61 reference statements)
6
22
0
2
Order By: Relevance
“…From these studies, it has therefore been suggested that myristic acid may be the most hypercholesterolemic saturated FA, followed by lauric acid (C12:0) and palmitic acid (C16:0). More recently, nutritional studies analyzing the effect of physiological doses (1.0% to 2.5% of dietary energy) of myristic acid have shown no effect on plasma total cholesterol in rats (Rioux et al, 2005), or a non-significant increase that reflected an increase in HDL-cholesterol but not LDLcholesterol in hamsters (Loison et al, 2002). As recently described in healthy men and women (Tholstrup, 2006), our results suggest that a moderate consumption of dairy products does not increase the risk of cardiovascular diseases (Dabadie et al, 2005;Tholstrup et al, 2003).…”
Section: Discussionsupporting
confidence: 70%
“…From these studies, it has therefore been suggested that myristic acid may be the most hypercholesterolemic saturated FA, followed by lauric acid (C12:0) and palmitic acid (C16:0). More recently, nutritional studies analyzing the effect of physiological doses (1.0% to 2.5% of dietary energy) of myristic acid have shown no effect on plasma total cholesterol in rats (Rioux et al, 2005), or a non-significant increase that reflected an increase in HDL-cholesterol but not LDLcholesterol in hamsters (Loison et al, 2002). As recently described in healthy men and women (Tholstrup, 2006), our results suggest that a moderate consumption of dairy products does not increase the risk of cardiovascular diseases (Dabadie et al, 2005;Tholstrup et al, 2003).…”
Section: Discussionsupporting
confidence: 70%
“…Consequently, HDL might be less capable to return cholesteryl esters to liver. Such an effect has been described in hamsters (Loison et al, 2002). The authors observed a negative correlation between the HDL-C concentration and the hepatic mass of scavenger receptor B1 (SR-B1), an HDL receptor, when animals were fed diets with increasing contents of myristic acid (from 0.6 up to 2.4% TEI).…”
Section: Discussionmentioning
confidence: 77%
“…For example, gene expression for receptors is sensitive to the hamster strain and to the lipid composing the diet (Loison et al, 2002). The hamster strain used in this study is recognised as forming fatty streaks and to be more sensitive to HC diets (Dorfman et al, 2003).…”
Section: Discussionmentioning
confidence: 97%